Competition injuries in young judo athletes - James, G.; Pieter, W.
The purpose of this study was to assess the injury profile of junior male and female judoka competing at the national level. Subjects consisted of 417 boys and 270 girls participating in the UK National Individual Judo Championships in 1996. Simple check-off forms were used to collect the injury data, including injury type, location, and mechanism. Non-parametric statistical procedures were used to determine the differences in injury rates between boys and girls as well as between body region within gender. The girls (52.1/1,000 athlete-exposures) sustained more injuries than the boys (39.8/1,000 athlete-exposures) (p = 0.047). The boys incurred most injuries to the head and neck region (16.2/1,000 athlete-exposures) and the girls to the upper extremities (19.7/1,000 athlete-exposures). The most common injury type in the boys was the strain (9.6/1,000 athlete-exposures) and in the girls, the contusion (18.5/1,000 athlete-exposures). The major injury mechanism in the boys was receiving a throw (13.3/1,000 athlete-exposures) and in the girls, groundwork (12.7/1,000 athlete-exposures). Total injury rates in this sample are among the lowest in junior combative sports athletes.